2009
DOI: 10.1074/jbc.m805101200
|View full text |Cite
|
Sign up to set email alerts
|

Monocytic Leukemia Zinc Finger (MOZ) Interacts with p53 to Induce p21 Expression and Cell-cycle Arrest

Abstract: Upon DNA damage, p53 can induce either cell-cycle arrest or apoptosis. Here we show that monocytic leukemia zinc finger (MOZ) forms a complex with p53 to induce p21 expression and cell-cycle arrest. The levels of the p53-MOZ complex increased in response to DNA damage to levels that induce cell-cycle arrest. MOZ(-/-) mouse embryonic fibroblasts failed to arrest in G1 in response to DNA damage, and DNA damage-induced expression of p21 was impaired in MOZ(-/-) cells. These results suggest that MOZ is involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 53 publications
3
65
0
1
Order By: Relevance
“…Indeed, it was recently shown that interactions between AML1/RUNX1 and MLL provide epigenetic regulation of gene expression in normal hematopoiesis and in leukemia (Huang G, personal communication) (Huang et al, 2008). MOZ is also associated with other transcription factors such as RUNX2, C/EBPa, C/EBPb, c-Jun, NF-kB, Nrf2/MafK and p53 (Pelletier et al, 2002;Ohta et al, 2005Ohta et al, , 2007Katsumoto et al, 2006;Chan et al, 2007;Rokudai et al, 2009). In addition, it was reported that MLL is a protein partner of p53 and HCF-1 in a cell cycle-dependent manner (Tyagi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was recently shown that interactions between AML1/RUNX1 and MLL provide epigenetic regulation of gene expression in normal hematopoiesis and in leukemia (Huang G, personal communication) (Huang et al, 2008). MOZ is also associated with other transcription factors such as RUNX2, C/EBPa, C/EBPb, c-Jun, NF-kB, Nrf2/MafK and p53 (Pelletier et al, 2002;Ohta et al, 2005Ohta et al, , 2007Katsumoto et al, 2006;Chan et al, 2007;Rokudai et al, 2009). In addition, it was reported that MLL is a protein partner of p53 and HCF-1 in a cell cycle-dependent manner (Tyagi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…81 The MOZ-CBP (CREB-binding protein) FP of t(8;16) AML also decreases p53 acetylation, thus mitigating p53 transcriptional activity, which probably yields the downregulation of several p53-related microRNAs, such as miR-34a. 82,83 In CML-Ph 11 blast-phase leukemia wtp53 inactivation is mediated by p53 deacetylation via SIRT1 (HDAC-III) upregulation and by MDM2 upregulation via BCR-ABL-induced La-antigen overexpression. 68,84 Another inactivating mechanism is operated by MOZ-TIF2 of inv(8) AML, which causes CBP mislocalization from PML bodies, depletion of its cellular levels, and reduction of CBPdependent p53 transcriptional activity.…”
Section: Aml With Chromosomal Translocationsmentioning
confidence: 99%
“…Associated factors present within these complexes may also contribute to the acetylation specificity of these nonhistone substrates. A few targets have been identified for the MYST acetyltransferase family (for a detailed review, see (Sapountzi and Cote 2011), including the p53 tumor suppressor protein, which can be acetylated on different lysine residues by these enzymes (Sykes et al 2006;Tang et al 2006Tang et al , 2008Li et al 2009;Rokudai et al 2009Rokudai et al , 2013. The MOF MYST acetyltransferase has been shown to be part of two separate complexes, MOF-MSL and MOF-MSL1v1 (Smith et al 2005;Li et al 2009).…”
Section: Conflicting Reports On Specificity Of Histone Modifiersmentioning
confidence: 99%